Determinants of breast screening participation using small-area data in South Australia: gaining past and future insights from geospatial evidence - Ming Li; Deborah van Gaans; Muktar Ahmed; Anh-Minh Nguyen; Michelle Reintals; Andrew Holmes; David Roder (Cancer Causes & Control, 2025)
Purpose To profile breast screening participation at small-area (SA2) level in South Australia (SA) and capture local variations in socio-economic factors, access to healthcare, and cultural influences screening behaviors in ways that larger administrative units might overlook. Methods SA2 demographic (2016 Census) and breast screening data in SA (2014–2015) were linked and analyzed. The dependent variable, biennial screening participation (ages 50–74 years), was classified as “low” if below the SA-wide biennial participation rate of 58%. Independent variables included SA2-level sociodemographic factors (e.g., socio-economic status, residential remoteness, country of birth) derived from Census data. Stepwise multivariable logistic regression was used to estimate the adjusted odds ratios (aORs) for low screening participation associated with SA2 demographic characteristics. Results BreastScreen SA participation for the 164 SA2 areas was 50.6%, ranging from 41.1% for ages 55–59 to 67.8% for ages 60–64. Indicators of low participation included disadvantaged socio-economic quintile (aOR increasing to 17.00, 95% CI 9.84–29.36 for quintiles 3–5 compared with the least disadvantaged quintile 1), non-metropolitan residence (aOR 4.94, 95% CI 2.30–10.60), and mortgage/rental stress in low-income households (aOR increasing to 6.59, 95% CI 3.34–13.00 for the third compared with first stress tertile). Areas providing more unpaid care support for disabled/aged people had reduced odds of low screening participation (aOR 0.41, 95% CI 0.24–0.70). Characteristics indicating low odds of low screening included a higher proportion of Australian born (tertile 2, aOR 0.52, 95% CI 0.30–0.88, and tertile 3, aOR 0.27, 95% CI 0.11–0.67). Conclusion Further model that aims to improve breast screening participation need to be explored at both individual and SA2 levels. Potential cultural and linguistically diverse (CALD), Indigenous, and socio-economic indicators could be drawn from the newly available ABS-managed PLIDA platform. More contemporary SA2 and screening data should also be used for prospective evaluation.

Metabolic profiling reveals enrichment of health-related metabolites in yoghurt by variation of strain consortium - Sandro Christensen; David Biedermann; Zahra Sattari; Thomas Roder; Mireille Tena-Stern; Carola Blaser; Pascal Fuchsmann; Ueli von Ah; Barbara Walther; Rémy Bruggmann; Stephanie C. Ganal-Vonarburg; Guy Vergères; et al. (Food Bioscience, 2025)

The effect of general practice contact on cancer stage at diagnosis in Aboriginal and non-Aboriginal residents of New South Wales - David Banham; David Roder; Sandra Thompson; Anna Williamson; Freddie Bray; David Currow (Cancer Causes & Control, 2023)
Purpose Older age, risks from pre-existing health conditions and socio-economic disadvantage are negatively related to the prospects of an early-stage cancer diagnosis. With older Aboriginal Australians having an elevated prevalence of these underlying factors, this study examines the potential for the mitigating effects of more frequent contact with general practitioners (GPs) in ensuring local-stage at diagnosis. Methods We compared the odds of local vs. more advanced stage at diagnosis of solid tumours according to GP contact, using linked registry and administrative data. Results were compared between Aboriginal ( n = 4,084) and non-Aboriginal ( n = 249,037) people aged 50 + years in New South Wales with a first diagnosis of cancer in 2003–2016. Results Younger age, male sex, having less area-based socio-economic disadvantage, and fewer comorbid conditions in the 12 months before diagnosis (0–2 vs. 3 +), were associated with local-stage in fully-adjusted structural models. The odds of local-stage with more frequent GP contact (14 + contacts per annum) also differed by Aboriginal status, with a higher adjusted odds ratio (aOR) of local-stage for frequent GP contact among Aboriginal people (aOR = 1.29; 95% CI 1.11–1.49) but not among non-Aboriginal people (aOR = 0.97; 95% CI 0.95–0.99). Conclusion Older Aboriginal Australians diagnosed with cancer experience more comorbid conditions and more socioeconomic disadvantage than other Australians, which are negatively related to diagnosis at a local-cancer stage. More frequent GP contact may act to partly offset this among the Aboriginal population of NSW.

Patterns of comorbidities in women with breast cancer: a Canadian population-based study - Huah Shin Ng; Agnes Vitry; Bogda Koczwara; David Roder; Mary L. McBride (Cancer Causes & Control, 2019)

Impact of hormone replacement therapy use on mammographic screening outcomes - Kerri R. Beckmann; Gelareh Farshid; David M. Roder; Janet E. Hiller; John W. Lynch (Cancer Causes & Control, 2013)

Estimating prevalence of distant metastatic breast cancer: a means of filling a data gap - Mark S. Clements; David M. Roder; Xue Qin Yu; Sam Egger; Dianne L. O’Connell (Cancer Causes & Control, 2012)

Epidemiology of neuroendocrine cancers in an Australian population - Colin Luke; Timothy Price; Amanda Townsend; Christos Karapetis; Dusan Kotasek; Nimit Singhal; Elizabeth Tracey; David Roder (Cancer Causes & Control, 2010)

A case–control study of the protective benefit of cervical screening against invasive cervical cancer in NSW women - Baohui Yang; Stephen Morrell; Yeqin Zuo; David Roder; Elizabeth Tracey; Paul Jelfs (Cancer Causes & Control, 2008)

Multiple primary cancers of separate organ sites: implications for research and cancer control (Australia) - Adrian Heard; David Roder; Colin Luke (Cancer Causes & Control, 2005)

A critical analysis of reasons for improved survival from invasive cutaneous melanoma - Colin Glen Luke; Brendon John Coventry; Erwin Joseph Foster-Smith; David Murray Roder (Cancer Causes & Control, 2003)

In Vivo and in Vitro Assessment of Baseline Blood-Brain Barrier Parameters in the Presence of Novel Nanoparticles - Paul R. Lockman; Joanna Koziara; Karen E. Roder; Jennifer Paulson; Thomas J. Abbruscato; Russell J. Mumper; David D. Allen (Pharmaceutical Research, 2003)